2018
DOI: 10.1038/s41598-018-32533-9
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin is effective in reducing mortality for critically ill patients with sepsis: a causal mediation analysis

Abstract: Ulinastatin has been found to have anti-inflammatory effect for patients with sepsis. However, its clinical effects were conflicting. The study aimed to investigate the cost-effectiveness of ulinastatin and to perform mediation analysis to explore the proportion of the total effects that can be explained by inflammatory responses. This is a retrospective study involving critically ill patients with sepsis from January 2014 to July 2017. A total of 263 patients were included in the study, involving 179 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Ulinastatin is a glycoprotein which can be obtained from human urine or produced synthetically. Proteolytic enzymes, including trypsin, elastase, and plasmin can be effectively inhibited by ulinastatin, lipase, and amylase, thus relieving the systemic inflammatory response and diminishing the severity of pancreatitis (9)(10)(11)(12). However, the dose-response effect of ulinastatin in SAP has not been established.…”
Section: Original Articlementioning
confidence: 99%
“…Ulinastatin is a glycoprotein which can be obtained from human urine or produced synthetically. Proteolytic enzymes, including trypsin, elastase, and plasmin can be effectively inhibited by ulinastatin, lipase, and amylase, thus relieving the systemic inflammatory response and diminishing the severity of pancreatitis (9)(10)(11)(12). However, the dose-response effect of ulinastatin in SAP has not been established.…”
Section: Original Articlementioning
confidence: 99%
“…UTI can also suppress MAPK-signaling pathway, which mediates the release of inflammatory cytokines such as TNF-α, IL-1, and IL-6 (Inoue and Takano, 2010; Fang et al, 2018). Recently, a retrospective study of 263 critically ill patients with sepsis found that 28-day mortality decreased significantly with UTI (Xu et al, 2018). The authors concluded that 35% of the total effect of UTI was associated with the reduction in C-reactive protein (CRP), a major marker of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Ulinastatin can reduce the pro-inflammatory levels (including TNF-α, IL-6, and IFN-γ), increase the anti-inflammatory factor IL-10 level (Tao et al, 2017), and promote the balance between proinflammatory and anti-inflammatory responses, thus blocking the cytokine storm induced by the vicious circle of inflammatory responses. Animal studies suggest that high-dose ulinastatin achieves a comparable anti-inflammatory effect to glucocorticoids (Xu et al, 2018). In 2017, a meta-analysis of eight RCTs suggested that ulinastatin combined with thymosin α1 (Tα1) in sepsis patients suppressed pro-inflammatory factor production, reduced the Acute Physiology and Chronic Health Evaluation (APACHE) II score, shortened the durations of mechanical ventilation, and improved the 28-days survival rate (Liu et al, 2017).…”
Section: Ulinastatinmentioning
confidence: 99%